RNA sequencing supports distinct reactive oxygen species-mediated pathways of apoptosis by high and low size mass fractions of Bay leaf (Lauris nobilis) in HT-29 cells. Issue 8 (5th August 2015) - Rodd, Annabelle L.; Ververis, Katherine; Sayakkarage, Dheeshana; Khan, Abdul W.; Rafehi, Haloom; Ziemann, Mark; Loveridge, Shanon J.; Lazarus, Ross; Kerr, Caroline; Lockett, Trevor; El-Osta, Assam; Karagiannis, Tom C.; et al.
<x xml:space="preserve">Abstract</x> DNA double strand breaks mediated by high mass bay leaf fraction in HT-29 cells.